The Performance of a Consumption Augmented Asset Index in Ranking Households and Identifying the Poor - Ngo, Diana; Christiaensen, Luc (World Bank, Washington, DC, 2018)
Asset ownership indices are widely used as inexpensive proxies for consumption. This paper shows that these indices can be augmented using dichotomous indicators for consumption, which are equally easy to obtain. The paper uses multiple rounds of Living Standards Measurement Study surveys from Malawi, Uganda, Rwanda, Tanzania, and Ghana to construct indices with different item subcategories and performs a meta-analysis comparing the indices to per capita consumption. The results show that the standard asset indices, which are derived from durable ownership and housing characteristic indicators, perform well in urban settings. Yet, in rural samples and when identifying the extreme poor, household rankings and poverty classification accuracy can be meaningfully improved by adding indicators of food and semi-durable consumption. The study finds small improvement from using national weights in urban samples but no improvement from using alternative construction methods. With most of Africa’s poor concentrated in rural areas, these are important insights.